Differentiating Predictive Validity and Practical Utility for the Australian Adaptation of the Youth Level of Service/Case Management Inventory - McGrath, Andrew James (Criminal justice and behavior, 2018)
The predictive validity for the Australian Adaptation of the Youth Level of Service/Case Management Inventory was tested in a large sample (N = 4,401) of community-based juvenile offenders in New South Wales, Australia. First, we compared gender and ethnic subgroups on domain, total scores, and predictive validity. Both similarities and modest differences emerged in mean scores across subgroups. The pattern of predictive validity results showed comparable indices by gender and ethnic subgroups. Second, we supplemented our quantitative method with a review of 26 case files with the lowest risk scores and a 1-year reoffense, and 25 case files with the highest risk scores and no 1-year reoffense. We discuss implications of the findings for improving the predictive validity and practical utility of risk-need assessment with juvenile offenders.